Religion as a source of legitimacy of power and its influence on the distribution of welfare - Anrivika, Gerry Ismail; Waehama, Muhammad Roflee (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This study aims to analyze how religion is utilized as a source of legitimacy for power and its impact on the distribution of welfare. Religion serves as both a moral and political instrument that can either enhance or hinder social justice. This research employs a qualitative approach with a descriptive-analytical method and a literature review to examine relevant theories and empirical cases. The findings reveal that religion plays a dual role in governance and welfare policies. On one hand, it is employed by political authorities to legitimize power, shaping policies that reinforce social structures. On the other hand, religious organizations actively contribute to welfare distribution through philanthropy and social services. However, the allocation of welfare resources based on religious identity often leads to exclusivity, deepening socio-economic disparities. The study concludes that while religion holds transformative potential in promoting social justice, its role in governance must be managed inclusively to prevent reinforcing inequalities. Therefore, a collaborative approach between the state, religious institutions, and civil society is necessary to ensure that religion’s role in legitimizing power contributes positively to equitable welfare distribution. Contribution: By advocating for collaborative efforts among the state, religious institutions, and civil society, this research provides a valuable framework for promoting equitable welfare distribution and mitigating socio-economic disparities linked to religious identity.